Fracture resistance of the deposited metal under dynamic and cyclic loading; Structural Integrity and Life; Vol. 24, № 2 - Leshchinsky L. K. Leonid Konstantinovich; Ivanov V. P. Vitaly Petrovich; Lavrova E. V. Elena Vladimirovna; Ilyashchenko D. P. Dmitry Pavlovich; Verkhoturova E. V. Elena Viktorovna (2024, 2024)
Title screen